How do you find all the zeros of f(x)=6x^4-5x^3-12x^2+5x+6f(x)=6x4−5x3−12x2+5x+6 given 1 and -1 as zeros?
1 Answer
Aug 14, 2016
The remaining zeros are
Explanation:
f(x) = 6x^4-5x^3-12x^2+5x+6f(x)=6x4−5x3−12x2+5x+6
Since we are told that
6x^4-5x^3-12x^2+5x+66x4−5x3−12x2+5x+6
=(x-1)(6x^3+x^2-11x-6)=(x−1)(6x3+x2−11x−6)
=(x-1)(x+1)(6x^2-5x-6)=(x−1)(x+1)(6x2−5x−6)
To factor the remaining quadratic we can use an AC method:
Find a pair of factors of
The pair
6x^2-5x-66x2−5x−6
=(6x^2-9x)+(4x-6)=(6x2−9x)+(4x−6)
=3x(2x-3)+2(2x-3)=3x(2x−3)+2(2x−3)
=(3x+2)(2x-3)=(3x+2)(2x−3)
Hence zeros